EFL Reading Materials Revisited: The Role of Teaching Processes, Individual Learning Prerequisites, and Textbook Use - Putri, Rr. Aurel Ramadhani; Emaliana, Ive; Suwarso, Pratnyawati Nuridi (Journal of Education Reseach and Evaluation, 2024)
The intensive reading module's instruction underscores the need to change based on the new curriculum guidelines, outcome-based education (OBE), which concentrates on student-centered learning. Based on this research’s grand theory, this can be achieved by investigating the teaching activity's process and students’ individual learning beliefs. This research aimed to analyze these factors as a part of need analysis. The study used a mixed-method approach. The data were collected using questionnaires, interviews, and a module analysis checklist based on OBE principles. The respondents comprised 164 third and fourth-year Indonesian students who took an intensive reading class and one lecturer who taught parallel intensive reading classes. The data were analyzed qualitatively and quantitatively. The study results showed that students have sophisticated epistemic beliefs in learning this course, and there is a significant correlation between the proposed reading strategy and students’ epistemic beliefs. Therefore, as the new reading strategy proposed, CSR should be implemented appropriately. Moreover, the findings revealed that the intensive reading classes did not apply the appropriate reading strategy that aligns with students’ learning beliefs and OBE principles in its implementation. In addition, students showed positive attitudes toward the proposed reading strategy. Furthermore, the module analysis indicated several poor indications that should be changed to meet the OBE principles and the student’s learning needs. These findings are the basis for developing the module analysis based on the needs of students. Due to the study’s scope and limitations, further research is recommended.